Process improvement for efficient and accurate reporting - Dizon, Ria (Animo Repository, 2023)
A lack of efficient and effective processes could lead to inconsistent quality, higher errors, and harm a business's success. Standard operating procedures can reduce errors, ensure consistency, and increase efficiency and accuracy. This integrative action research aims to improve the financial and income tax reporting efficiency and accuracy of Zambales Bookkeeping Agency. The first-person, second-person, and third-person data collection methods were applied in this integrative action research. Lewin's Change Management Model, ADKAR Model, and PDCA cycle are the third-person frameworks that guided the insider action researcher and her collaborators. This integrative action research has demonstrated that establishing a systematic guideline would help individuals be more accountable and avoid errors for higher-quality reports. Overall, this integrative action research highlights the importance of collaborative interventions to identify the focal issue and manage the necessary changes integral to an organization's success. Keywords: Action research, process improvement, standard operating procedure, efficiency and accuracy, Lewin’s change management model, PDCA Cycle, ADKAR Model, professional skepticism, journal entries, training with journal entries